Assessment of Intrarenal Artery Doppler Resistive Index in Normotensive Patients and Patients with Essential Hypertension - Obinna E. Abonyi; Uloma B. Nwogu; Vitus K. Ika; Julius A. Agbo; Beatrice U. Maduka; Sharonrose O. Nwadike (International Journal of Medicine and Health Development)
Background: Hypertension, a significant global health issue, often leads to organ damage, particularly affecting the kidneys. The renal resistive index (RRI) is a useful tool for assessing kidney function in hypertensive patients, but population-specific data are scarce. Objectives: This study aimed to compare the RRI in normotensive and hypertensive subjects in South-East Nigeria and examine its correlation with age and body mass index (BMI). Materials and Methods: A cross-sectional study was conducted on two hundred (200) participants consisting of one hundred (100) each of normotensive and hypertensive adult subjects. Doppler ultrasound was used to measure the RRI, with the average of three readings considered the final value. Age and BMI data were collected for analysis. Data were analyzed using SPSS version 24.0. Demographic variables were expressed as means ± standard deviations. Pearson’s correlation coefficient assessed the associations between RRI, age, and BMI. Results: The mean RRI for the right and left kidneys in normotensive subjects was 0.63 ± 0.42 and 0.61 ± 0.03, respectively, and in hypertensive subjects, it was 0.74 ± 0.04 and 0.73 ± 0.05. There was a statistically significant difference in RRI values between the two groups (P < 0.000). No significant correlation was found between RRI, age, and BMI. Conclusion: Hypertensive subjects in Southeast Nigeria had higher RRI values compared to normotensive subjects, highlighting the importance of regular RRI monitoring in hypertensive management to improve the clinical outcomes.